Understanding mental phenomena in the mythological and religious symbols of the Eastern Slavs - PREDKO, Denys (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. In the current climate of heightened interest in ethnic identity, traditional culture, and folk mentality, studying ancient beliefs about the soul and mental phenomena allows us to gain a deeper understanding of the formation of psychological experience, moral norms, and belief systems. It is especially important to understand how folk traditions interpreted phenomena such as consciousness, the afterlife, good and evil, and mental health, since these ideas formed the cultural basis for the perception of the individual in society. Methods. The historical-cultural method (when studying mythological and religious ideas in the context of a specific historical era); the psychological-hermeneutic method (when interpreting mythological beliefs as a reflection of deep psychological processes). Results. It has been established that the mytho-religious conceptions of the Eastern Slavs regarding the soul and psychic phenomena formed an integrated sacred-symbolic model of the human inner world, in which the psyche was conceptualized as a dynamic, supernaturally determined process. It was found that the soul was perceived as a mobile and multivariant entity capable of separating from the body, transforming its imagery, and transitioning between different dimensions of existence. The study reveals that mental states and experiences were interpreted through natural elements (fire, breath, etc.), which endowed them with sacred and moral-normative significance. It is demonstrated that ceremonial and ritual practices, by navigating boundary situations, performed a regulatory function aimed at maintaining spiritual equilibrium and restoring harmony between the individual and the sacred world. Conclusions. It has been determined that the essence and specificity of the interconnection between mythological and religious components in East Slavic conceptions of the soul lie in the fact that myth provided a symbolic language for conceptualizing the psyche, while the religious component transformed this language into an effective system of faith, cult, and moral regulation. Together, these ideas functioned as mechanisms for consolidation, regulation, and reproduction (through folklore and rituals) in everyday life, overcoming boundary situations and forming a holistic model of the human inner world.